2009
DOI: 10.1016/j.tet.2009.03.085
|View full text |Cite
|
Sign up to set email alerts
|

The application of vinylogous iminium salt derivatives to efficient formal syntheses of the marine alkaloids lamellarin G trimethyl ether and ningalin B

Abstract: Studies directed at the synthesis of lamellarin G trimethyl ether and ningalin B via vinylogous iminium salt derivatives are described. The successful strategy relies on the formation of a 2,4-disubstituted pyrrole or a 1,2,3,4-tetrasubstituted pyrrole from a vinylogous iminium salt or vinylogous iminium salt derivative. Subsequent transformations of these highly substituted pyrroles lead to efficient and regiocontrolled formal syntheses of the respective pyrrole containing natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Lamellarin G trimethyl ether (6) is the substance often used as a synthetic target for proof of concept for new synthetic methods and approaches. We have previously reported 24 a vinamidinium salt based approach to this important target and we decided to use our new synthetic methodology (Scheme 5) for the preparation of a key pyrrole intermediate (28), which we previously described 24 in our formal synthesis of lamellarin G trimethyl ether (6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lamellarin G trimethyl ether (6) is the substance often used as a synthetic target for proof of concept for new synthetic methods and approaches. We have previously reported 24 a vinamidinium salt based approach to this important target and we decided to use our new synthetic methodology (Scheme 5) for the preparation of a key pyrrole intermediate (28), which we previously described 24 in our formal synthesis of lamellarin G trimethyl ether (6).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting product is iodinated at C-3 (27) and this material undergoes cross-coupling to produce a tetrasubstituted pyrrole (28), which we previously prepared 24 via the vinamidinium salt route and was fully characterized. The spectral properties for the product (28) of our new methodology were identical to those we reported earlier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrolysis was quite sluggish, to our surprise, and actually the reaction was not completed even after 3 days under the influence of KOH (10 equiv) in refluxing aqueous dioxane. 9 After much trials we found that the hydrolysis was conducted efficiently in a mixed solvent, THF/MeOH/H 2 O (2:2:1), at 50 o C in the presence of an excess amount of KOH (10 equiv) within shorter time (36-42 h).…”
Section: Resultsmentioning
confidence: 99%